Delayed Onset Malignant Hyperthermia after Sevoflurane - K. Sanem Cakar Turhan; Volkan Baytaş; Yeşim Batislam; Oya Özatamer (Case Reports in Anesthesiology)
Malignant hyperthermia is a hypermetabolic response to inhalation agents (such as halothane, sevoflurane, and desflurane), succinylcholine, vigorous exercise, and heat. Reactions develop more frequently in males than females (2 : 1). The classical signs of malignant hyperthermia are hyperthermia, tachycardia, tachypnea, increased carbon dioxide production, increased oxygen consumption, acidosis, muscle rigidity and rhabdomyolysis. In this case report, we present a case of delayed onset malignant hyperthermia-like reaction after the second exposure to sevoflurane.